A biointelligence system for identifying potential disease outbreaks. - Xiaohui Zhang (IEEE Engineering in medicine and biology magazine)
The development of public health surveillance systems requires multidisciplinary knowledge and advanced technologies. Scientific Technologies Corp. has developed the NH Pharmaceutical Sales Surveillance (NHPSS) for the New Hampshire Department of Health and Human Services (NH DHHS). The NHPSS was developed as a distributed information system. In addition to the database server, enterprise application servers and the Web-browser-based user interface, its architecture features knowledgebase technology, a new dynamic system model with rule systems, and automated data analysis in supporting public health surveillance. Internet mapping was also embedded in the system to provide for spatial analysis. Since its pilot application, started in December of 2002 in the Bureau of Communicable Disease Control and Surveillance, NH DHHS, the NHPSS has assisted NH DHHS in successful detections of gastrointestinal and respiratory events. This article first introduces the methodology and the technology in the NHPSS development. Next, the system functionalities are introduced. Then, a new dynamic system model with a rule system for public health surveillance is described in detail. Finally its application and preliminary results are summarized.